2013
DOI: 10.1111/jocn.12260
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job satisfaction and intention to leave current employment among registered nurses in a teaching hospital

Abstract: Methods for enhancing nurses' job satisfaction are vital to promote the long-term retention of nurses within organisations. Attention must be paid to the needs of younger nurses, as they represent the majority of the nursing workforce and often have lower satisfaction and greater intention to leave than older nurses do. Strategies to nurture younger nurses, such as providing opportunities for further education, greater management decision-making capabilities and flexible working environment, are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
82
5
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 43 publications
10
82
5
10
Order By: Relevance
“…Although "professional qualification" did not show differences in either the NWI-R or IWS between the technical and higher education levels in the present study, other studies have identified an association between work satisfaction, level of education and environment of practices (2,10,(14)(15) . A Brazilian study performed in several units of a university hospital, which also included the ICU, aiming to investigate work satisfaction, indicated that such satisfaction was associated with the technical level of qualification and workplace.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Although "professional qualification" did not show differences in either the NWI-R or IWS between the technical and higher education levels in the present study, other studies have identified an association between work satisfaction, level of education and environment of practices (2,10,(14)(15) . A Brazilian study performed in several units of a university hospital, which also included the ICU, aiming to investigate work satisfaction, indicated that such satisfaction was associated with the technical level of qualification and workplace.…”
Section: Discussioncontrasting
confidence: 45%
“…The work dynamics also caused the expectations of higher education professionals not to be met and their level of satisfaction to be low (10) . Thus, the development of one's level of professional qualification allows one to achieve higher hierarchical positions, and promotes work satisfaction through the encouragement of autonomy and capacity-building for decision-making, especially when reflecting better results achieved and patient safety (2,(14)(15) . Regarding "material/technological resources" and "human resources", the proportion of professionals for each of these variables, 41.84% and 21.64% respectively, who considered them to be sufficient, assessed the environment more positively and showed greater work satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explaned that higher prevalence of emotional exhaustion in these nurses. Recently published studies [34,35,36] have shown that working shifts has a strong influence on nurses' job satisfaction, burnout, intention to leave the hospital or even the profession. Wisetborisut et al (2014) found that the prevalence of burnout in shift workers was 25% compared with 15% in non-shift workers, and having more sleeping hours per day was associated with a lower odds of burnout among shift workers [37].…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with another study's finding, according to which the lack of growth opportunity in a hospital may reduce nurses WS (17) . On the other hand, institutions that facilitate this growth come to increase WS (18) . Being a public institution, and so having the remarkable stability that allows workers to keep an employment relationship for many years, Caism has a great amount of workers that, throughout their careers, acquired professional qualifications different from the performed functions of the original hiring.…”
Section: Discussionmentioning
confidence: 99%